2005
DOI: 10.1182/blood-2004-11-4435
|View full text |Cite
|
Sign up to set email alerts
|

Fusion proteins comprising annexin V and Kunitz protease inhibitors are highly potent thrombogenic site-directed anticoagulants

Abstract: The anionic phospholipid, phosphatidyl-Lserine (PS), is sequestered in the inner layer of the plasma membrane in normal cells. Upon injury, activation, and apoptosis, PS becomes exposed on the surfaces of cells and sheds microparticles, which are procoagulant. Coagulation is initiated by formation of a tissue factor/factor VIIa complex on PS-exposed membranes and propagated through the assembly of intrinsic tenase (factor VIIIa/factor IXa), prothrombinase (factor Va/factor Xa), and factor XIa complexes on PS-e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
38
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 66 publications
1
38
0
Order By: Relevance
“…NP-7 contains a cluster of positively charged residues in the N-terminus and specifically binds to anionic phospholipids, preventing thrombin formation by the prothrombinase (Andersen et al, 2004). Finally, a bifunctional fusion protein containing Kunitz and annexin domains was shown recently to inhibit the initiation of blood coagulation (Chen et al, 2005).…”
Section: Group 1: Basic-tail Proteins (Btp)mentioning
confidence: 99%
“…NP-7 contains a cluster of positively charged residues in the N-terminus and specifically binds to anionic phospholipids, preventing thrombin formation by the prothrombinase (Andersen et al, 2004). Finally, a bifunctional fusion protein containing Kunitz and annexin domains was shown recently to inhibit the initiation of blood coagulation (Chen et al, 2005).…”
Section: Group 1: Basic-tail Proteins (Btp)mentioning
confidence: 99%
“…24,25 An alternative epitope for clot-targeting has been recently described: Phosphatidyl-L-serine/phosphatidylethanolamine, which is exposed on activated platelets and microparticles. 26 A 3-to 10-fold increase in anticoagulant potency could be achieved by this targeting strategy. 26 Another recent approach used P-selectin, which is expressed on activated platelets as well as on activated endothelial cells, as an epitope to target Desmodusrotundus salivary plasminogen activator alpha1.…”
Section: Discussionmentioning
confidence: 99%
“…5,7,8) Following injury to the endothelium and vessel wall, platelets adhere rapidly to the sub-endothelial matrix, then become activated and form the primary hemostatic plug. 9,10) In the meanwhile, phospholipids such as phosphatidylserine (PS) are rapidly exposed on the membrane surfaces of activated platelets. [11][12][13][14] The activated platelets provide anionic surfaces for the assembly and catalysis of intrinsic tenase (VIIIa/IXa), prothrombinase (Va/Xa), and XIa complexes, leading to explosive generation of thrombin and consolidation of the fibrin-platelet plug.…”
mentioning
confidence: 99%
“…[26][27][28][29] Many efforts have been made to construct ANXV based chimeras for evaluation of their targeting effect at a potential thrombus. 6,10,30,31) Staphylokinase (SAK) is one of the promising blood clot dissolving agents. 1,6,[32][33][34] Although the thrombolytic potency of SAK has been found to be comparable to that of tPA, clinical trials have indicated that SAK has a superior fibrin specificity.…”
mentioning
confidence: 99%
See 1 more Smart Citation